The Effect of Sex, Menstrual Cycle Phase, and Monophasic Oral Contraceptive Pill Use on Local and Central Arterial Stiffness in Young Adults - Priest, Stacey (My University, 2017)
Arterial stiffness is a predictor of cardiovascular disease (CVD), and can be measured locally by carotid artery β-stiffness index and centrally by carotid-femoral pulse wave velocity (cfPWV). Previous investigations examining sex differences in these measures have resulted in inconsistent findings, and despite the prior evidence for an influence of sex hormones on the vasculature, have not controlled for menstrual cycle phase in women. Arterial stiffness is also understudied across the menstrual cycle and in women who use oral contraceptive pills (OCPs), despite current use of OCPs by more than 100 million women worldwide. The objectives of this thesis were 1) to examine potential sex differences in local and central arterial stiffness, 2) to explore potential differences in arterial stiffness between a natural menstrual cycle (NAT) and an OCP cycle (OCP), 3) to determine the relationship between duration of OCP use and arterial stiffness, and 4) to examine the repeatability of local and central arterial stiffness across three weeks in men, and across a natural menstrual cycle and an OCP cycle in women. Fifty-three healthy participants (22±3 years) were recruited into three groups (20 men, 15 NAT, 18 OCP). Men attended one visit, NAT attended three visits across the duration of one menstrual cycle (menstrual, follicular, and luteal phases), and OCP attended three visits at the same relative days as NAT across one pill cycle (placebo pill phase, and active pill phase: 2 visits). At each visit, a blood sample was collected to identify serum sex hormone concentrations, and β-stiffness index and cfPWV were also assessed. Men had a higher β-stiffness index than NAT and OCP (p<0.01), whereas cfPWV was not different between groups (p=0.22). There was no difference between NAT and OCP at any timepoint across a cycle for β-stiffness index (p=0.26) or cfPWV (p=0.41), and no association between duration of OCP use and β-stiffness index (r=0.003, p=0.99) or cfPWV (r =-0.261, p=0.30). These results indicate that while men have elevated local arterial stiffness, there are no sex differences in central arterial stiffness. There were also no arterial stiffness differences across a cycle between women who experience natural menstrual cycles or women who use OCPs, despite fluctuations in sex hormone concentrations, and no relationship between duration of OCP use and arterial stiffness. The findings from this study highlight the importance of assessing both local and central arterial stiffness when considering sex differences. Furthermore, future studies related to arterial stiffness may not have to control for menstrual cycle phase, OCP phase, or duration of OCP use in women.